Handwritten receipt signed by Ferdinand Hiller - Hiller, Ferdinand, 1811-1885:::Creator::::::::::::; Halpern, C. M.::::::::::::::: (2021)
Handwritten receipt for 10 francs from C. M. Halpern in the hand of Ferdinand Hiller, in French, with his signature, dated 7 September 1879.